Sudan : Enhanced Heavily-Indebted Poor Countries Initiative-Preliminary Document. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
Sudan, with the support of the international community, is seeking to implement an ambitious reform program to address major macroeconomic imbalances and support sustainable, inclusive growth. A new transitional government was established in the wake of the 2019 revolution with the mandate to carry out sweeping reforms to reverse decades of economic and social decline. The government is pursuing a transformational reform agenda focused on: (i) achieving internal peace based on inclusion, regional equity, and justice; (ii) stabilizing the economy and correcting the large macroeconomic imbalances; and (iii) providing a foundation for future rapid growth, development, and poverty reduction. The government has achieved important milestones, most prominently a peace agreement with almost all internal armed opposition groups in October 2020 to end 17 years of conflict. It has also agreed to ambitious reforms and policy adjustments in the context of an International Monetary Fund (IMF) Staff Monitored Program (SMP) that meets the Upper Credit Tranche (UCT) conditionality standard and an International Development Association (IDA) Development Policy Financing (DPF) operation. Furthermore, on December 14, 2020, Sudan was officially removed from the United States State Sponsors of Terrorism List (SSTL), ending almost three decades of international isolation. While positive changes are underway, political contestation over power sharing arrangements remains acute. It is critical for Sudan to take advantage of a still favourable political economy to tackle its macroeconomic imbalances and put itself on a sustainable development trajectory.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Sudan